Reducing Metabolic Dysregulation in Obese Latina and/or Hispanic Breast Cancer Survivors Using Physical Activity (ROSA) Trial: A Study Protocol - Gonzalo-Encabo, Paola; Wilson, Rebekah L.; Kang, Dong-Woo; Norris, Mary K.; Uno, Hajime; Christopher, Cami N.; Chow, Christina; Sami, Nathalie; Fox, Frank S.; Ligibel, Jennifer A.; Dieli-Conwright, Christina M. (Frontiers in Oncology, 2022)
Background: Latina and Hispanic breast cancer survivors (LHBCS) are at increased risk for long-term complications and poorer metabolic health, including metabolic dysregulation (MetD) before and following breast cancer diagnosis. MetD can increase risk of cancer recurrence, death, and comorbid conditions by increasing inflammation and cancer cell proliferation. While exercise improves physical fitness and metabolic outcomes in breast cancer survivors, there is a lack of studies including underrepresented and disadvantaged minority groups such as LHBCS. Methods: Our 12-month randomized (exercise or attention control) controlled trial (the ROSA trial) aims to utilize a progressive combined aerobic and resistance exercise program to improve MetD, insulin resistance, and visceral adiposity among obese LHBCS. We aim to recruit 160 women with Stage I-III breast cancer who are sedentary, centrally obese, and have completed treatment (e.g., surgery, radiation, chemotherapy) prior to enrollment. Participants randomized to the exercise group receive 16-weeks of virtually supervised aerobic and resistance training, followed by 16-weeks of unsupervised home-based aerobic and resistance exercise, and 16-weeks of follow-up. The attention control group receive a 12-month home-based stretching program. Primary and secondary outcomes are measured every 4-weeks during study visits. Discussion: The ROSA trial is the first exercise oncology trial targeting high-risk sedentary, obese LHBCS to improve MetD-related outcomes. Results of this trial will help illuminate how exercise impacts health-related outcomes, survivorship, and recurrence, and inform future exercise oncology guidelines to reduce health disparities among minority cancer survivors.